2022
DOI: 10.1186/s40168-022-01236-9
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effect of epigenetic modification in plant–microbe interactions: modification of DNA methylation induced by plant growth-promoting bacteria mediates promotion process

Abstract: Background Soil microbiomes are considered a cornerstone of the next green revolution, and plant growth-promoting bacteria (PGPB) are critical for microbiome engineering. However, taking plant-beneficial microorganisms from discovery to agricultural application remains challenging, as the mechanisms underlying the interactions between beneficial strains and plants in native soils are still largely unknown. Increasing numbers of studies have indicated that strains introduced to manipulate microb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 73 publications
1
38
0
Order By: Relevance
“…For example, Feng et al (2016) reported that Cd-responsive gene expression may be modified by DNA methylation in rice exposed to Cd. Our recent study of pokeweed also proved that DNA methylation variation induced by bacteria can regulate gene expression ( Chen et al, 2022 ). Although transcriptome analysis of P. americana L. in response to Cd stress have been reported before ( Chen et al, 2017 ), they did not pay attention to the effect of DNA methylation on gene expression and did not compare the difference of DEG under Mn and Cd stress.…”
Section: Discussionmentioning
confidence: 91%
See 4 more Smart Citations
“…For example, Feng et al (2016) reported that Cd-responsive gene expression may be modified by DNA methylation in rice exposed to Cd. Our recent study of pokeweed also proved that DNA methylation variation induced by bacteria can regulate gene expression ( Chen et al, 2022 ). Although transcriptome analysis of P. americana L. in response to Cd stress have been reported before ( Chen et al, 2017 ), they did not pay attention to the effect of DNA methylation on gene expression and did not compare the difference of DEG under Mn and Cd stress.…”
Section: Discussionmentioning
confidence: 91%
“…Epigenetic variation which can regulate phenotypic variation could be one potentially important way for plant in response to environmental changes ( Niederhuth and Schmitz, 2014 ; Wibowo et al, 2016 ; Li et al, 2021 ). DNA methylation is one of the main epigenetic mechanisms enabling adaptation of plants in complex environments ( Niederhuth and Schmitz, 2014 ; Chang et al, 2019 ; Perrone and Martinelli, 2020 ; Li et al, 2021 ; Chen et al, 2022 ). Changes of DNA methylation in response to environmental stresses can be relatively stable, and establish a DNA methylation-dependent stress memory to the offspring ( Wibowo et al, 2016 ; Williams and Gehring, 2017 ; Sudan et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations